Population Dynamics of Vibrio fischeri during Infection of Euprymna scolopes - McCann, Jessica (American Society for Microbiology, 2003)
The luminous bacterium Vibrio fischeri colonizes a specialized light-emitting organ within its squid host, Euprymna scolopes. Newly hatched juvenile squid must acquire their symbiont from ambient seawater, where the bacteria are present at low concentrations. To understand the population dynamics of V. fischeri during colonization more fully, we used mini-Tn7 transposons to mark bacteria with antibiotic resistance so that the growth of their progeny could be monitored. When grown in culture, there was no detectable metabolic burden on V. fischeri cells carrying the transposon, which inserts in single copy in a specific intergenic region of the V. fischeri genome. Strains marked with mini-Tn7 also appeared to be equivalent to the wild type in their ability to infect and multiply within the host during coinoculation experiments. Studies of the early stages of colonization suggested that only a few bacteria became associated with symbiotic tissue when animals were exposed for a discrete period (3 h) to an inoculum of V. fischeri cells equivalent to natural population levels; nevertheless, all these hosts became infected. When three differentially marked strains of V. fischeri were coincubated with juvenile squid, the number of strains recovered from an individual symbiotic organ was directly dependent on the size of the inoculum. Further, these results indicated that, when exposed to low numbers of V. fischeri, the host may become colonized by only one or a few bacterial cells, suggesting that symbiotic infection is highly efficient.